Artificial intelligent based damping controller optimization for the multimachine power system: a review - Hannan, Muhammad Abdul; Islam, Naz Niamul; Mohamed, Azah; Lipu, Molla Shahadat Hossain; Ker, Pin Jern; Rashid, Muhammad Mahbubur; Shareef, Hussain (Institute of Electrical and Electronics Engineers Inc., 2018)
Power system oscillation is a major threat to the stability of an interconnected power system. The safe operation of a modern power system is largely related to the success of oscillation damping. However, damping controller development is a constraint-based multimodal optimization problem, which is relatively difficult to resolve utilizing conventional optimization algorithms. This review presents a critical examination of different damping schemes and a stability analysis of a damping controller to solve these existing problems and enhance the performance of a multi-machine power system. This review also describes different approaches used to derive the objective function formulation. Consequently, a comprehensive review of the optimized objective functions and techniques are explained on the basis of their topologies, types, execution times, control difficulties, efficiencies, advantages, and disadvantages to develop intelligent damping controllers for the systems. Furthermore, the optimization strategies for the damping controller are reviewed along with the benefits and limitations, current issues and challenges, and recommendations. All the highlighted insights of this review will hopefully lead to increasing efforts toward the development of an advanced optimized damping controller for future high-tech multi-machine power systems.